Analisis Perawatan Mesin Bending Menggunakan Metode Failure Mode And Effect Analysis (FMEA) dan Fault Tree Analysis (Fta) di PT. XYZ - Ade Ismail Firzatulloh; Tarman Tarman; Afif Fawa Idul Fata (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
This study analyzes failures in the bending machine at PT. XYZ and determines maintenance priorities to reduce downtime and improve production efficiency. The company often faces repeated breakdowns, especially in hydraulic and control components, which negatively impact productivity. To address these issues, the research applies Failure Mode and Effect Analysis (FMEA) and Fault Tree Analysis (FTA). The study employs a descriptive qualitative approach using downtime and repair data from September 2024 to February 2025. FMEA was conducted to identify failure modes, effects, and causes, and to calculate the Risk Priority Number (RPN) as a basis for prioritization. FTA was then applied to trace root causes by mapping logical relationships among contributing factors leading to the top event. Recommendations were formulated with the 5W+1H method to propose preventive maintenance actions. The results indicate that the hydraulic valve is the most critical component, with an RPN value of 504 due to oil contamination. The main causes include damaged filters, improper oil usage, and lack of a cooling system. The hydraulic cylinder seal and back gauge were also found to contribute significantly to machine failures. FTA analysis revealed root causes such as inadequate maintenance procedures, unsuitable materials, and insufficient inspections. The proposed improvements involve regular replacement of oil filters, structured lubrication schedules, installation of oil coolers, and technician training to strengthen compliance with standard procedures. Overall, the integration of FMEA and FTA provides a systematic approach to identify critical components and root causes, enabling PT. XYZ to implement preventive strategies that minimize failures, reduce downtime, and improve bending machine performance sustainably.